HISTORY OF US MEDIA PARTICIPATION IN THE CRISIS OF THE SOVIET STATE (1950-1991) - Sharof Rashidov; Saidov Ilhomjon Muhiddinovich; Yuldashev Akmal Kurbanbayevich (American Journals, 2023)
The principal weapon of the cold war, which developed between the USA and the USSR after World War II and has grown in intensity over time, is the media, which is discussed in this article. It primarily discusses the early Western media's impact on the USSR, the Soviet press's response to such anti-communist ideas and their effects, as well as the factors that led to and contributed to the communist thought spreading throughout the entire Union.
Keywords: Centar Europe, Voice of America, USSR, Communist Party, Soviet Union, Central Apparatus, Iron Curtain